(untitled) (Journal of history, 2022)
The history and ethnography of the Kazakh people aroused great interest from Russian travelers, officials, military officers and researchers for various purposes, thus remaining the main object of study. Their writings contain valuable information about the traditional hunting of the Kazakhs. Scientists who dealt with this problem in different periods relied on the works of Russian researchers and tried to introduce them into scientific circulation as much as possible. However, many of their works were not fully considered as sources on the history of hunting of the Kazakhs, they did not receive a proper assessment, making up only as works on this problem. In this article, we are trying to introduce into scientific circulation information about the traditional hunting of the Kazakhs, which is contained in the works of Russian researchers of the 18-19th centuries, and to reveal their scientific significance. The source base of the article is the works of Russian researchers and archival materials of the Central State Archive of the Republic of Kazakhstan. The source study method used in the analysis of these materials made it possible to study in more detail information about the traditional hunting of the Kazakhs and make an analysis at the scientific level. The given data made it possible to determine the development of Kazakh hunting in the 18-19th centuries, to reveal its regional features, methods of hunting, the reasons for its transformation and turning it into a source of profit.